Electronic Word-of-Mouth: Effect of Gender, Expertise, and Susceptibility to Interpersonal Influence on Customers’ Motivation to Seek Online Hotel Reviews in Saudi Arabia - Alghamdi, Essam (2017)
Abstract Word of mouth—online or offline—has become a dominant force in the market place, and it is now a very important in the hospitality industry because the services being offered are intangible products, which are hard to evaluate before their usage. Companies in hospitality industries have realised the impact of eWOM communication on sale and revenue and have used it as an important predictor of market success. This dissertation focuses on the influence of online hotel reviews in Saudi Arabia, including the motivations to seek online hotel reviews. To gain a meaningful picture of these motivations, this dissertation aims to examine the impact of gender, expertise and customer’s susceptibility to interpersonal influence (CSII) on motivations to seek online hotel reviews. The dissertation methods consisted of a combination of related literature reviews from verified sources together with empirical research, using questionnaires. The findings from this research show that females tended to be driven more than males towards reviewing online hotel reviews, regardless of their expertise level; that participants with high experience are more motivated to seek online reviews than those with low or medium expertise; and that customer susceptibility to informational influence (CSII) has a significant impact on motivational factors, with risk reduction as the strongest motivator. The greater the CSII was, the greater was the likelihood of seeking hotel reviews. This dissertation recommends that hotel managers continuously check for online reviews by their past clients. Such a plan will make them more able to understand the concerns among of prior consumers and confirm they are doing the right thing regarding service.